The dynamics of soil-soluble nitrogen and soil-retained nitrogen in greenhouse soil. (2nd January 2017) - Duan, Pengpeng; Zhang, Yuling; Cong, Yaohui; Xu, Wenjing; Yu, Na; Zhang, Yulong
ABSTRACT: Field experiments were conducted to determine the effects of nitrogen (N) fertilization and manure addition on the soil-soluble nitrogen (SSN) (soil mineral N (SMN); soil-soluble organic N (SSON)) and soil-retained N (SRN) (soil fixed ammonium; soil microbial biomass N). The combined application of manure and inorganic N (different N fertilizer rates: M3N0, M3N1, M3N2, and M3N3; different manure rates: M0N2, M1N2, M2N2, and M3N2) was used in a greenhouse fertilization experiment. SSN and SRN increased with increasing N rate up to M3N2. SSON decreased with increasing manure rate and was the highest in the M1N2, whereas SMN and SRN were the highest in the M3N2, and increased with increasing manure rate on all sampling dates. Both SSN and SRN declined significantly with increasing soil depth in the different application rates of manure ( p < .05). Moreover, the SSN and SRN significantly varied with plant growth and followed a different pattern during the growing season. SSN and FA peaked in the first ear fruit period, but SMBN was at its highest level in the second ear fruit period. There was a significant positive relationship ( p < .05) between SSN and SRN throughout the plant growing season, and the annual apparent loss of N in the M3N3 was the highest. The combined application of inorganic N fertilizer and manure at an appropriate rate may be an effective strategy for maintaining the long-term health of greenhouses.